Prototype of Automatic Tobacco Chopper Using PLC Omron CPM1-A Type - Dewi Cahya Febrina (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2023)
Tobacco is the main raw material used to make cigarettes. Increasing of cigarette sales which have continued until now has led to an increasing of tobacco produced by tobacco farmers. Region of East Java has the largest percentage of tobacco producers and most of the peoples that work as tobacco farmers. Some of them still carried out the chopping process manually, thus requires more energy and longer time. This research is carried out by chopping tobacco leaves that have been dried and stacked with a thickness of 4mm. The procedure is carried out by pressing the start button, then conveyor moves to bring the container to the chopper. The container which attached to the magnet will be stop and detected by the reed switch sensor. The conveyor rotation is controlled by a DC motor gearbox and the operation of the chopper blades is controlled by a power window motor. All the chopping process is controlled using PLC